Cytomegalovirus induced pseudotumor of the colon in a renal transplanted patient - Syed Mudassir Laeeq; Zain Majid; Rajesh Mandhwani; Nasir Hasan Luck; Muhammed Mubarak (Society of Diabetic Nephropathy Prevention, 2017)
Cytomegalovirus or CMV is a common viral pathogen that infects the gastrointestinal tract and is seen in various forms in immunocompromised individuals. It is often isolated from individuals having weakened or suppressed immune system because of either human immunodeficiency virus (HIV) infection, transplantation, malignancies or immune suppressing medications. Here we describe a case of gastro-intestinal CMV infection in a renal transplant patient that had presented as colonic pseudo tumor. As CMV induced pseudo-tumors may respond to medical therapy, physicians treating immunosuppressed individuals should be wary of it for better management of the condition.